농촌 주민의 노인 돌봄 제공 의향과 수용의사금액 분석 - 김남훈; 조승연; 하혜지 (농촌경제, 2021)
Community care led by rural residents is emerging as an alternative to overcome the flawed care system for the elderly in rural areas. However, no paper has studied whether rural residents would participate in providing care for the rural elderly. In this study, we investigate whether rural residents are willing to provide community care to the elderly who need care and evaluate the amount of the willingness to accept it. For this purpose, we conducted empirical analyses by using (ordered) logistic and interval regressions with the survey of 586 farmers living in rural areas. The result shows that 60% of respondents were willing to provide care to the elderly and the amount of the willingness to accept (WTA) for providing care was around 5,000 won. It also shows that residents who had economic difficulties or needed non-agricultural income tended to participate in care. Female and younger residents also expressed a higher amount of WTA　because they could work with higher wages in other jobs. For the policy implication, we suggest that the government cooperate with rural communities to support sufficient compensation for part-time care services so that more rural residents can participate in community care.